A novel balloon technique to induce intra‐abdominal hypertension and its effects on cardiovascular parameters in a conscious dog model. Issue 4 (13th June 2018) - Jang, Min; Son, Won‐gyun; Jo, Sang‐min; Kim, Hyunseok; Shin, Chi Won; Lee, Inhyung
Abstract: Objective: To evaluate a new balloon technique to induce intra‐abdominal hypertension (IAH) and abdominal compartment syndrome in a conscious dog model, and to evaluate the effect of intra‐abdominal pressure (IAP) on cardiovascular, respiratory, and arterial blood gas values in conscious dogs with IAH. Design: Prospective, experimental study. Setting: University‐based small animal research facility. Animals: Six healthy Beagle dogs, 4 males, and 2 females. Interventions: A new balloon device designed for this study using a Foley urethral catheter and latex balloon was placed in the abdominal cavity. Consecutive measurements of IAP were made by measuring the intravesicular pressure. The abdomen was inflated with air to IAPs of 10, 15, 20, and 25 mm Hg. Heart rate, respiratory rate, systolic arterial blood pressure, and arterial blood gases were evaluated at baseline and at 15, 30, 45, 60, 120, 240, and 300 minutes after IAP increase. Measurements and Main Results: The air insufflated into the intra‐abdominal balloon device significantly increased the IAP and led to sustained IAH. The respiratory rate increased significantly ( P < 0.05) when IAP was increased to 15, 20, and 25 mm Hg. Although heart rate, systolic arterial blood pressure, PaO2, and PaCO2 did not show statistically significant differences between baseline and posttreatment values over time, the dogs with increased IAP showed a distended abdomen and apparent discomfort, and 4/6 (67%) vomited. After measurement of IAP, air was removed. There were no adverse effects noted after removal of the balloon device. Conclusion: The balloon device was successfully insufflated and led to sustained IAH in conscious dogs. This balloon technique does not require general anesthesia for instillation or removal of gas after installment. An acute IAP increase in normal conscious dogs induced discomfort, vomiting, and increased respiratory effort.